DISKRESI (FREIES ERMESSEN) OLEH PEJABAT PEMERINTAH RAMBU HUKUM, ALAT UKUR KEABSAHAN, DAN KECERMATAN DALAM PENGGUNAANNYA - Ridwan Ridwan (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
There is no law of which articles can embrace all aspects of the community life and various unpredicted events. Discretion is intended to implement the vague written laws (vagenormen) at the concret situation so the government function can be conducted in flexibility and effectivity. Even though the discretion is not based on the clear written law, or there is no written text at all, discretion is still bounded to the principle of validity (rechtmatigheid), in term of the authorithy, procedure, and substance. The legal sign of the discretion is clear and universal, but it is often adjusted to be in line with the needs of the users of the discretion. That kind of discretion is out of the real discretion context; it is a kind of authorithy and law abuse. The problem is not on the law, but it is on the manner of the discretion users.